2015
DOI: 10.1002/pd.4698
|View full text |Cite
|
Sign up to set email alerts
|

Impact of prenatal screening and diagnostic testing on trends in Down syndrome births and terminations in Western Australia 1980 to 2013

Abstract: Prenatal testing in Western Australia has reduced the birth prevalence of Down syndrome despite an increased rate of Down syndrome pregnancies. Most women for whom a prenatal diagnosis of fetal Down syndrome is made, chose to terminate the pregnancy (93%), and this proportion has not changed over the study period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 19 publications
(41 reference statements)
2
26
0
Order By: Relevance
“…Such differences may reflect religious and personal preferences in the study populations. The TOP rate for trisomy 21 (93.8%) in the current study was similar to that in other recent population‐based or multicenter studies in Australia, China, England and Wales, and Netherlands (92%–94%), although it was higher than that in the population‐based studies reported from Canada and the United States (67%) . Among cases of prenatally diagnosed trisomy 21 before 22 weeks of gestation, the live birth rate was only 2.6%.…”
Section: Discussionsupporting
confidence: 85%
“…Such differences may reflect religious and personal preferences in the study populations. The TOP rate for trisomy 21 (93.8%) in the current study was similar to that in other recent population‐based or multicenter studies in Australia, China, England and Wales, and Netherlands (92%–94%), although it was higher than that in the population‐based studies reported from Canada and the United States (67%) . Among cases of prenatally diagnosed trisomy 21 before 22 weeks of gestation, the live birth rate was only 2.6%.…”
Section: Discussionsupporting
confidence: 85%
“…A population-based study from the United Kingdom found that pregnancies for both T13 and T18 per 1000 registered births increased from 0.08 to 0.23 and 0.20 to 0.65 respectively, as the percentage of mothers over 35 years increased from 6 to 15% during 1985–2007 [2]. In Western Australia, the rate of fetal Down syndrome pregnancies increased from 1.1 to 2.9 per 1000 births; births for women aged 35+ years increased from 8% to 20% during 1980–2013 [3]. Aside from maternal age, earlier surveillance as well as wide-spread practice of prenatal screening and diagnosis also contributed to the increased identification of chromosomal abnormalities in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, the total prevalence of T21, T18 and T13 all increased over time because of maternal age [1]. In Western Australia, a three-fold increase in the presence of T21 was observed from 1980–2013, corresponding to the steady rise in the number of mothers over 35 years of age [3]. In the Northern Health Region of England, the incidence of T18 and T13 increased together with a rise in the number of mothers over 35 years of age [2].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study from Western Australia also found a significant reduction in the rate of liveborns with Down syndrome [7]. The aim of this study was to evaluate the impact of the implementation of PNS in the Northern Netherlands on the detection of common trisomies: T21, T18 and T13 with respect to both first and second trimester PNS, time of diagnosis and pregnancy outcome.…”
Section: Introductionmentioning
confidence: 99%